Representations of German Culture and Society on Social Media in the Post-truth Era - Dian Rizky Azhari (Nexus Publishing, 2025)
Known as the era of biased truth and lies in information, the post-truth era seems to bring new problems in the world of foreign language learning, especially German language. The large amount of content on social media that is considered a cultural document, and a depiction of German society is basically not a true representation, if we refer to the phenomenon of the existence of immigrants from outside Germany who also produce German-language content on social media. Meanwhile, German language teachers and students today cannot be separated from activities in cyberspace, such as reading articles, consuming content in German-language, learning the language through social media, or even contents about the culture itself. Based on this notion, this study attempts to critically examine German-language content on social media related to the daily lives of people in Germany to see the influence of immigrant’s cultural viewpoints on the content. Research findings indicate that the multicultural aspects present within society in Germany significantly influence the representation of German culture and society on social media platforms. However, on the other hand, such representations may distort the understanding of German culture and society among novice German language learners who consume this content uncritically.